The Influence of the Social Inquiry Learning Model on the Creative Dance Learning Outcomes of Class VIII Students - Rahmawati Rahmawati; Dwi Junianti Lestari; Syamsul Rizal (EDUJAVARE: International Journal of Educational Research, 2026)
Civil This research is motivated by the low learning outcomes of class VIII students in creative dance material at SMP Negeri 18 Kota Serang. The average student score (74.5) was still below the Minimum Completeness Criteria (KKM = 75). This problem was supported by the use of conventional teacher-centered learning models, making students tend to be passive and less enthusiastic in following dance learning. The purposes of this study were: (1) to describe the learning process using the Social Inquiry model on creative dance material for class VIII students at SMPN 18 Kota Serang; and (2) to determine the effect of the Social Inquiry learning model on learning outcomes of creative dance material for class VIII students at SMPN 18 Kota Serang. This study uses a Quasi Experimental Design method with a pretest-posttest control group design. The research sample was class VIII A as the experimental class (30 students) and class VIII C as the control class (30 students). The research instrument used multiple choice test questions. Data analysis used Chi Square normality test, F test homogeneity test, and t test hypothesis test. The results showed that the average posttest score of the experimental class (86.73) was higher than the control class (67.42). The t-test results obtained t count (2.84) > t table (1.67) at a significance level of 5%, so H1 was accepted. The conclusion of this study is that there is a significant effect of using the Social Inquiry learning model on the learning outcomes of creative dance material for class VIII students at SMP Negeri 18 Kota Serang.